Rigorous and efficient full-wave analysis of trapezoidal patch antennas. - Bilotti, F. (IEEE Transactions on antennas and propagation)
A rigorous full-wave analysis in the spectral domain for trapezoidal patch antennas is presented. Particularly, a new set of entire domain basis functions for an efficient implementation of the method of moments (MoM) is carried out by properly imposing the boundary conditions. The simulated results obtained through the presented method are compared to the measurements showing a good agreement. Finally, a parametric analysis of the main antenna features (matching, radiation pattern, cross-polarization levels) is also carried out